2005
DOI: 10.1088/0031-9155/50/23/014
|View full text |Cite
|
Sign up to set email alerts
|

High-precision dosimetry for radiotherapy using the optically stimulated luminescence technique and thin Al2O3:C dosimeters

Abstract: The potential of using the optically stimulated luminescence (OSL) technique with aluminium oxide (Al(2)O(3):C) dosimeters for a precise and accurate estimation of absorbed doses delivered by high-energy photon beams was investigated. This study demonstrates the high reproducibility of the OSL measurements and presents a preliminary determination of the depth-dose curve in water for a 6 MV photon beam from a linear accelerator. The uncertainty of a single OSL measurement, estimated from the variance of a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 31 publications
4
51
0
7
Order By: Relevance
“…Schembri and Heijmen (2007) who have investigated OSL film dosimeters found an inter film response variation in a range of 1% to 3.2%. Better results have been reported by Yukihara et al (2005) in a reproducibility test with ten packages, each containing five OSL dosimeters, irradiated in a 6MV photon beam. They found that the maximum difference between the mean package readings from the overall mean was 0.7%.…”
Section: Basic Oslds Characteristicsmentioning
confidence: 85%
“…Schembri and Heijmen (2007) who have investigated OSL film dosimeters found an inter film response variation in a range of 1% to 3.2%. Better results have been reported by Yukihara et al (2005) in a reproducibility test with ten packages, each containing five OSL dosimeters, irradiated in a 6MV photon beam. They found that the maximum difference between the mean package readings from the overall mean was 0.7%.…”
Section: Basic Oslds Characteristicsmentioning
confidence: 85%
“…The OSL process is similar to that of thermoluminescence (TL), with the primary difference being that an optical stimulus is used in OSL instead of a thermal or heat stimulus in the TL process to induce luminescence of the irradiated material. After irradiation, light-emitting diodes (LEDs) supply the optical energy required to release the stored OSL signal; this signal is directly proportional to the dose absorbed by the dosimeter (Yukihara et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16]. More recently, OSL of borate and silicates doped with Ce, Eu, Sm and Cu ions have been reported [8][9][10][11][12]. Attempts are also made to study materials like BeO [17], NaMgF 3 :Eu [18], MgO:Tb [19], LiMgPO 4 :Tb,B [20], LiAlO 2 [21], YAG:C [22], Cu doped Alkali fluorosilicates [23][24][25], Li 3 PO 4 :Cu [26], SiO 2 :Ag [27], KBr:Eu [28], (NH 4 ) 2 SiF 6 :Tl [29], LiAlO 2 :Tb,Ce [30,31], ZnAl 2 O 4 :Tb [32], MgAl 2 O 4 :Tb [33] etc.…”
Section: Introductionmentioning
confidence: 98%
“…Carbon doped alumina (Al 2 O 3 :C) is the most popular phosphor material with the highest potential for OSL dosimetry due to its excellent dosimetric properties [1,2]. The application of OSL property of a-Al 2 O 3 :C single crystal has been established in personnel dosimetry [3,4], environmental dosimetry [5], medical dosimetry [6][7][8][9] and space dosimetry [10,11]. Although many OSL phosphors have been developed for dosimetric applications, the research is mainly centered on natural/synthetic quartz, feldspars, oxides, fluorides, chlorides etc.…”
Section: Introductionmentioning
confidence: 99%